Church Youth Sexuality in Surabaya: Teachings, Attitudes, and Behaviors - Mulya, Teguh Wijaya (ANIMA Indonesian Psychological Journal, 2010)
The aim of this study is to describe the teachings regarding sexuality among Christian churches in Surabaya, sexual attitudes, and sexual behaviors of the church youths. Six church leaders from six churches were interviewed and 267 church youths filled anonymous sexual attitude and sexual behavior questionnaire. The result shows that most of the churches adopt conservative teachings. These teachings are consistent with sexual attitudes of the church youths. However, the behaviors are not always consistent with the attitudes, mainly on the autonomous sexual behaviors. In term of sexual abstinence, 85.8% of respondents report never engaged in sexual intercourse in their lifetime. The implications and limitations are discussed. Penelitian ini bertujuan mendeskripsikan pengajaran tentang seksualitas, sikap seksual, dan perilaku seksual remaja-pemuda gereja Kristen di Surabaya. Enam pemimpin dari enam gereja diwawancarai dan 267 remaja-pemuda gereja mengisi kuesioner anonim tentang sikap seksual dan perilaku seksual. Hasil penelitian menunjukkan bahwa kebanyakan gereja partisipan mengadopsi pengajaran yang konservatif. Pengajaran ini konsisten dengan sikap seksual remaja-pemuda gereja. Namun perilaku seksual remaja-pemuda gereja tersebut tidak selalu konsisten dengan sikapnya, terlebih pada perilaku seksual otonomus. Terkait pemantangan seksual, sejumlah 85.8% reponden melaporkan tidak pernah melakukan hubungan seksual (intercourse). Implikasi dan keterbatasan penelitian didiskusikan.